Wet Chemical Synthesis of Graphene - Eigler, Siegfried; Enzelberger-Heim, Michael; Grimm, Stefan; Hofmann, Philipp; Kroener, Wolfgang; Geworski, Andreas; Dotzer, Christoph; Röckert, Michael; Xiao, Jie; Papp, Christian; Lytken, Ole; Steinrück, Hans-Peter; et al. (Advanced Materials, 2013)
A suitable technology for the preparation of graphene based on versatile wet chemistry is presented for the first time. The protocol allows the wet chemical synthesis of graphene from a new form of graphene oxide that consists of an intact hexagonal extgreeks-framework of C-atoms. Thus, it can be easily reduced to graphene that is no longer dominated by defects.